If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5 + -3x + -1(-4x + 6) = -1(8x + 11) + -1(3x + -10) Reorder the terms: 5 + -3x + -1(6 + -4x) = -1(8x + 11) + -1(3x + -10) 5 + -3x + (6 * -1 + -4x * -1) = -1(8x + 11) + -1(3x + -10) 5 + -3x + (-6 + 4x) = -1(8x + 11) + -1(3x + -10) Reorder the terms: 5 + -6 + -3x + 4x = -1(8x + 11) + -1(3x + -10) Combine like terms: 5 + -6 = -1 -1 + -3x + 4x = -1(8x + 11) + -1(3x + -10) Combine like terms: -3x + 4x = 1x -1 + 1x = -1(8x + 11) + -1(3x + -10) Reorder the terms: -1 + 1x = -1(11 + 8x) + -1(3x + -10) -1 + 1x = (11 * -1 + 8x * -1) + -1(3x + -10) -1 + 1x = (-11 + -8x) + -1(3x + -10) Reorder the terms: -1 + 1x = -11 + -8x + -1(-10 + 3x) -1 + 1x = -11 + -8x + (-10 * -1 + 3x * -1) -1 + 1x = -11 + -8x + (10 + -3x) Reorder the terms: -1 + 1x = -11 + 10 + -8x + -3x Combine like terms: -11 + 10 = -1 -1 + 1x = -1 + -8x + -3x Combine like terms: -8x + -3x = -11x -1 + 1x = -1 + -11x Add '1' to each side of the equation. -1 + 1 + 1x = -1 + 1 + -11x Combine like terms: -1 + 1 = 0 0 + 1x = -1 + 1 + -11x 1x = -1 + 1 + -11x Combine like terms: -1 + 1 = 0 1x = 0 + -11x 1x = -11x Solving 1x = -11x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '11x' to each side of the equation. 1x + 11x = -11x + 11x Combine like terms: 1x + 11x = 12x 12x = -11x + 11x Combine like terms: -11x + 11x = 0 12x = 0 Divide each side by '12'. x = 0 Simplifying x = 0
| 42.5/y=x | | 2=(3+x)+3(2) | | x^(-1/5)=(1/3) | | x^-1/5=1/3 | | 8x+41y+10=180 | | 2n/3=4 | | x-x+3x+x+30+28=40 | | 5h-7-3h=2(h-14) | | a^3-64= | | (2c+1)=(c-5) | | 4x^2+4y^2-16x+32y-20=0 | | (2c-1)=(c-5) | | 12y-18/2 | | 16x-3=68+13+4x | | 2x+4x+2x+1+5x-6=60 | | r/s=25 | | 9x+1=9(1)+2 | | (37b-8)-9(4b+4)=-2 | | 96.8639/883.3525= | | 1-0.4p=2 | | 3x-6=-7x-6 | | 1x+16+56=90 | | (7+y)(5y+3)= | | 11x+35+35=180 | | 3p-42=31 | | 1-0.4=2 | | 18x-4+4x=172 | | 8w+12-6w=5(w+3)-2w | | a^2-16a+63=0 | | .5x+4=-6 | | -1+4/25=-1 | | 4x*2c-4+4c=0 |